Carbon dioxide sorption by tetradecylamine supported on silica gel - Abu Tahari, Maratun Najiha; Lahuri, Azizul Hakim; Tengku Azmi, Tengku Sharifah Marliza; Yarmo, Mohd. Ambar (Malaysian Analytical Sciences Society, 2017)
Carbon dioxide emissions generated from fossil fuel-based power plants and other industries has reached 400 ppm in atmosphere. This negatively impact the environment, infrastructures and wildlife in particular. A lot of efforts are needed to produce CO2 gas sorbent in order to reduce high CO2 concentration. Therefore, porous silica gel (SG) is modified with amine compound for carbon dioxide capture. Calcinated silica gel functionalized with tetradecylamine (TDA) using wet impregnation has been developed as a porous media. The prepared sorbents is characterized by N2 physisorption technique Brunauer-Emmet-Teller analysis (BET). Significant changes in physical properties of the sorbents further ascertained the dispersion of TDA on the internal channels and external surface of the SG. Reactivity of porous sorbent towards CO2 was evaluated using isothermal CO2 adsorption desorption technique. This study shows 65TDA/SG enable to adsorb CO2 in the highest capacity which is 23.22 cm3CO2per gram sorbent. Moreover, CO2 capture consists of two type sorption which are physisorption and chemisorption. 55TDA/SG is the best sorbent in capturing CO 2by chemisorption (19.62 cm3CO2per gram adsorbent).